Modulation of the molecular arrangement in artificial and biological membranes by phospholipid-shelled microbubbles. (January 2017) - Carugo, Dario; Aron, Miles; Sezgin, Erdinc; Bernardino de la Serna, Jorge; Kuimova, Marina K.; Eggeling, Christian; Stride, Eleanor
Abstract: The transfer of material from phospholipid-coated microbubbles to cell membranes has been hypothesized to play a role in ultrasound-mediated drug delivery. In this study, we employed quantitative fluorescence microscopy techniques to investigate this phenomenon in both artificial and biological membrane bilayers in an acoustofluidic system. The results of the present study provide strong evidence for the transfer of material from microbubble coatings into cell membranes. Our results indicate that transfer of phospholipids alters the organization of molecules in cell membranes, specifically the lipid ordering or packing, which is known to be a key determinant of membrane mechanical properties, protein dynamics, and permeability. We further show that polyethylene-glycol, used in many clinical microbubble formulations, also has a major impact on both membrane lipid ordering and the extent of lipid transfer, and that this occurs even in the absence of ultrasound exposure.